Beta 2-microglobulin gene mutations: a study of established colorectal cell lines and fresh tumors. - Bicknell, D; Rowan, A; Bodmer, W (1994)
The technique of single-strand conformation polymorphism (SSCP) was used to screen a series of 37 established colorectal cell lines, 22 fresh tumor samples, and 22 normal DNA samples for mutations in the beta 2-microglobulin gene. Exon 1 (including the leader peptide sequence) and exon 2 were screened separately. Six of 37 colorectal cell lines and 1 of 22 fresh tumors were shown to contain mutations, whereas no mutations were detected in the normal DNA samples. Sequencing of these mutations showed that an 8-bp CT repeat in the leader peptide sequence was particularly variable, since 3 of the cell lines and one fresh tumor sample have deletions in this region. In the related cell lines, DLD-1 and HCT-15, two similar mutations were identified, a C-->A substitution in codon 10 and a G-->T mutation in the splice sequence of intron 1. Expression of beta 2-microglobulin was examined using a series of monoclonal antibodies in an ELISA system. Reduced expression correlated with a mutation in one allele of beta 2-microglobulin, whereas loss of expression was seen in instances where a line was homozygous for a mutation or heterozygous for two mutations.